2013
DOI: 10.1080/08952841.2013.838854
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence in Older Women in Spain: Prevalence, Health Consequences, and Service Utilization

Abstract: The purpose of this study is to estimate the prevalence of lifetime intimate partner violence (IPV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 31 publications
1
32
0
3
Order By: Relevance
“…Our findings of disproportionate experiences of psychological DV among women are consistent with the literature on violence in older adults(Duque, Leal, Marques, Eskinazi, & Duque, 2012;Laumann, Leitsch, & Waite, 2008). However, most studies of victimization in older adults have focused only on women(Bazargan-Hejazi et al, 2013;Bonomi et al, 2007;Chen et al, 2005;Chen, Rovi, Vega, Jacobs, & Johnson, 2009;Flood & Pease, 2009;Linos, Khawaja, & Al-Nsour, 2010;Montero et al, 2013;Stö ckl et al, 2012;Weeks & LeBlanc, 2011). Evidence from research on men is sufficiently strong to justify recommending the inclusion of a gender perspective in all analyses of DV in older populations(Dixon & Graham-Kevan, 2011; Esquivel-Santoveñ a & Dixon, 2012).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Our findings of disproportionate experiences of psychological DV among women are consistent with the literature on violence in older adults(Duque, Leal, Marques, Eskinazi, & Duque, 2012;Laumann, Leitsch, & Waite, 2008). However, most studies of victimization in older adults have focused only on women(Bazargan-Hejazi et al, 2013;Bonomi et al, 2007;Chen et al, 2005;Chen, Rovi, Vega, Jacobs, & Johnson, 2009;Flood & Pease, 2009;Linos, Khawaja, & Al-Nsour, 2010;Montero et al, 2013;Stö ckl et al, 2012;Weeks & LeBlanc, 2011). Evidence from research on men is sufficiently strong to justify recommending the inclusion of a gender perspective in all analyses of DV in older populations(Dixon & Graham-Kevan, 2011; Esquivel-Santoveñ a & Dixon, 2012).…”
supporting
confidence: 90%
“…Those who report being the victims of physical violence are more likely to experience incontinence, anxiety, sleeping problems, and stress (Bonomi et al, 2007;Hadeed & El-Bassel, 2006). With few exceptions, most research in older adults has been carried out in North America and Europe (Acierno et al, 2010;Bazargan-Hejazi, Medeiros, Mohammadi, Lin, & Dalal, 2013;Bonomi et al, 2007;Chen, Rovi, Vega, Jacobs, & Johnson, 2005;Hadeed & El-Bassel, 2006;Montero et al, 2013;Stö ckl et al, 2012;Weeks & LeBlanc, 2011;Yan & Chan, 2012), with few studies conducted in Latin American settings such as Colombia and Brazil (Abath, Leal, Filho, & Marques, 2010;Espíndola & Blay, 2007;Jú nior, 2010;Minayo, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…In the first place, the high prevalence of this type of conduct should be emphasised (Cadmus and Owoaje, 2012;Montero et al, 2013;Stockl, Watts and Penhale, 2012;Orte and Sánchez, 2012;Suelves, Jané and Plasència, 2010). Some authors estimate its prevalence at 29.4%, with an average duration of 21 years for women over the age of 55 (Montero et al, 2013).…”
Section: Resultsmentioning
confidence: 97%
“…Some authors estimate its prevalence at 29.4%, with an average duration of 21 years for women over the age of 55 (Montero et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, in US studies, women older than 55 years were more affected by IPV than younger women 7 , with intimate partners accounting for 13-50% of the abuse committed 8 . Similarly, in Spain, 29.4% of elderly women suffered this type of violence 9 . In Brazil, the prevalence of intimate partner violence in the study of elderly women and men was 5.9% for physical violence and 20.9% for psychological violence 10 , while in Brazil and Colombia, a study carried out with 60-74 year-olds, IPV found prevalence of psychological violence in women of 26.0% and 20.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%